The Transareolar–Periareolar Approach. Issue 9 (September 2016) - Zelken, Jonathan; Huang, Jung-Ju; Wu, Chih-Wei; Lin, Yi-Ling; Cheng, Ming-Huei
Abstract : Summary: The periareolar approach is limited by areolar diameter. Asian women typically have smaller areolae than Western women. Voluminous and form-stable silicone implants demand larger incisions. Zigzag transareolar approaches closely approximate the nipple and improve exposure, but scar appearance remains problematic, and there is a risk of ductal injury and capsular contracture. We prefer a zigzag incision that straddles the areolar border. Between 2013 and 2015, 11 augmentation mammoplasties (20 incisions) were performed through a transareolar–periareolar (TAPA) incision. The TAPA incision resembles 3 inverted V's that traverse the inferior areolar border. Outcomes were evaluated on the basis of photographs, clinical charts, and surveys. Women were 36 years old (range, 25–50). Silicone implants were used in 10 patients and saline in 1 patient. Implants were 270 cm 3, placed in subpectoral position in 6 patients and subglandular position in 5. Follow-up was 12.5 months (range, 5–20 mo); there were no hematomas or infections. There was 1 case each of seroma (9.1%) and unilateral capsular contracture (9.1%) after secondary mammoplasty. There was no implant malposition or contour deformity. There were no keloids or hypertrophic scars. Every patient was satisfied. Nipple sensation was maintained or heightened in 100% of patients surveyed. The incisions were 139% longer than 180-degree periareolar scars. TAPA scars were well tolerated in this series of Asian women. We did not observe malposition, infection, or sensory disturbances. Despite its peripheral position on the nipple–areola complex, there are not enough data to determine whether TAPA incisions reduce risks compared with traditional approaches.